Sliding behavior of high speed ball bearings based on improved nonlinear dynamic model. (December 2021) - Qian, Dongsheng; Xu, Xiaotian; Deng, Song; Jiang, Shaofeng; Hua, Lin
To accurately predict the dynamic behaviors of high speed ball bearings, an investigation on the sliding behavior of balls at high and low speeds, and light and heavy loads is necessary. However, existing nonlinear dynamic models fail to consider comprehensively key factors such as asperity and hydrodynamic tractions, time-varying friction coefficient and time-varying lubricant mode. In this work, these influencing factors are integrated into the nonlinear dynamic model to make it suitable for the working conditions of high and low speeds and light and heavy loads. The dynamic analysis provides the relation of angular speeds of balls with spin and sliding at light and heavy loads, also it reveals the number of pure rolling point under the combined effect of differential sliding and spin sliding. Research results provide a reliable mathematical model and theoretical bases for further studying the dynamic behaviors of high speed ball bearings.